Dike Inflation Process Beneath Sakurajima Volcano, Japan, During the Earthquake Swarm of August 15, 2015 - Koike, Midori; Nakamichi, Haruhisa (Frontiers in Earth Science, 2021)
Magma intrusion usually causes seismicity and deformation in the surrounding rock and often leads to eruptions. A swarm of volcano-tectonic (VT) earthquakes associated with rapid dike intrusion in hours occurred beneath Sakurajima volcano on August 15, 2015. We determined the hypocenters and focal mechanisms of the VT earthquake swarm. The distributions of pressure (P)- and tension (T)-axes of the azimuths of the mechanisms are also obtained. The results indicate spatiotemporal changes of the distributions of the hypocenters and P- and T-axes. The hypocenters are distributed at depths of 0.3–1 km and 7:00–10:30 JST, and are located at depths of 0.3–3 km and 10:30–12:00 during which the seismic activity is the largest. At 12:00–24:00, the hypocenters are distributed in shallow and deep clusters at depths of 0.2–1 km and 1.5–3.5 km, respectively. The dike induced rapid ground deformation and is located between the shallow and deep clusters. The strike and opening directions of the dike are parallel to the NE–SW and NW–SE directions, respectively, corresponding to the regional maximum and minimum compression stress. The T-axes of the shallow cluster are distributed parallel to the opening direction of the dike. The P-axes of the deep cluster exhibit a pattern corresponding to the NE–SW direction and the T-axes are distributed in the NW–SE direction. In contrast, a 90° rotated pattern of strike-slip faulting is also observed at the deep cluster at 12:00–24:00, where the P-axes are distributed in the NW–SE direction and the T-axes are distributed in the NE–SW direction. This reflects the change in the stress field due to the dike inflation during the earthquake generation, and indicates that the alteration of stress in the vicinity of the dike due to the dike inflation and VT earthquakes are induced by the differential stress exceeding the brittle fracture strength of the rock. Future seismic and deformation observations in volcanoes will verify whether the spatiotemporal changes of the hypocenters and focal mechanism shown by this study are unique features of rapid dike intrusion.